2020
DOI: 10.1029/2019jd031422
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analyses for the Retrievals of Ice Cloud Properties From Radiometric and Polarimetric Measurements in Sub‐mm/mm and Infrared Bands

Abstract: Simulations of the radiometric and polarimetric properties of ice clouds based on the Moderate Resolution Imaging Spectroradiometer (MODIS) Collection 6 ice cloud model (aggregates in conjunction with the gamma distribution) are performed at wavelengths in the Infrared (IR) and Submillimeter/Millimeter (sub‐mm/mm) regimes. The scattering/absorption/polarization properties from the precalculated database are incorporated into a radiative transfer model, the Atmospheric Radiative Transfer Model (ARTS). A number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Consequently, 1D radiative‐transfer simulation is sufficient in the passive‐only retrieval of column‐integrated properties, for example, ice water path (IWP) and cloud optical thickness (COT), in what can be recognized as one pixel of a cloud scene. For example, lookup tables for the top‐of‐the‐atmosphere brightness temperature differences (BTDs, which could be defined as the brightness temperatures under the clear sky minus that in the cloudy scene) and IWPs, COTs or effective particle sizes could be established at different atmospheric states (Mendrok et al ., 2009; Li et al ., 2017; Coy et al ., 2020). It was found that the retrieved IWPs would be affected by ice clouds' vertically heterogeneous properties.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, 1D radiative‐transfer simulation is sufficient in the passive‐only retrieval of column‐integrated properties, for example, ice water path (IWP) and cloud optical thickness (COT), in what can be recognized as one pixel of a cloud scene. For example, lookup tables for the top‐of‐the‐atmosphere brightness temperature differences (BTDs, which could be defined as the brightness temperatures under the clear sky minus that in the cloudy scene) and IWPs, COTs or effective particle sizes could be established at different atmospheric states (Mendrok et al ., 2009; Li et al ., 2017; Coy et al ., 2020). It was found that the retrieved IWPs would be affected by ice clouds' vertically heterogeneous properties.…”
Section: Introductionmentioning
confidence: 99%
“…The well-established impact of the oriented hydrometeors has encouraged several authors to emphasise the need for the incorporation of hydrometeor orientation into retrievals, based on microwave data [17,19,[21][22][23]. This has not yet occurred.…”
Section: Introductionmentioning
confidence: 99%